Body Mass Index (BMI) and Infectious/Febrile Episodes in Children with Intermediate Risk Acute Lymphoblastic Leukemia (IR ALL). (19th May 2019) - Chaber, Radosław; Latos-Grażyńska, Elżbieta; Ciebiera, Krzysztof; Łach, Kornelia; Tokar, Barbara; Cebulski, Józef; Trybucka, Katarzyna; Mazur, Artur
Abstract: The incidence of treatment related mortality in children with acute lymphoblastic leukemia (ALL) is reported to be between 2% and 4% with infections being the leading cause. Aim: To establish a relationship between body mass index at diagnosis (BMI 0), after protocol I therapy completion (BMI I) and the incidence rate ratio (IRR) of infectious/febrile episodes in children with ALL intermediate risk. Methods: Thirty one consecutive patients (2–18 years old, with a male to female ratio of 19/12) with newly diagnosed ALL that were treated uniformly according to ALL IC 2009 protocol were included in this analysis. Results: A BMI decrease of at least 5% during protocol I therapy and BMI 1 under 15th percentile score corresponds significantly with higher IRR (with P -values 0.04 and 0.006 respectively) during the whole intensive therapy. Conclusion: Some relationships between BMI reduction and higher IRR in ALL patients were found, but their significance is limited by the size of the group analyzed.